Spatiotemporal Characteristics of Reference Crop Evapotranspiration in Inner Mongolia from 1959 to 2018 - WANG Bin; QIAO Shuaishuai; LIU Jifa (Renmin Zhujiang)
To comprehensively understand the impact of climate change on reference crop evapotranspiration (ET0) in Inner Mongolia,the daily ET0 of 50 meteorological stations in Inner Mongolia in the past 60 years was calculated using the FAO Penman-Monteith formula,and further investigated spatiotemporal characteristics,interdecadal and cyclical changes of ET0 in Inner Mongolia.The results showed that the distribution trend of ET0 gradually decreased from west to east in Inner Mongolia,the multi-year average was 1 018 mm,while the climate tilt rate was 4.2 mm/10a,showing a significant upward trend.The sum of ET0 in spring,summer and autumn,the growing periods of crops,accounted for about 95% of the total annual value,while the spatial distribution was similar to the annual value.The annual average ET0 in various climate zones followed a descending order:ultra-arid climate zone,arid climate zone,semi-arid climate zone,dry and semi-humid climate zone,humid and semi-humid climate zone.The variation coefficients of the climate zones were low,showing weak variability,and abrupt changes occurred in different climate zones at the end of the 1990s.The ET0 change cycles were mainly 59a,14a and 24a.